2019
DOI: 10.1017/s0140525x19000098
|View full text |Cite
|
Sign up to set email alerts
|

Slowing life history (K) can account for increasing micro-innovation rates and GDP growth, but not macro-innovation rates, which declined following the end of the Industrial Revolution

Abstract: Baumard proposes that life history slowing in populations over time is the principal driver of innovation rates. We show that this is only true of micro-innovation rates, which reflect cognitive and economic specialization as an adaptation to high population density, and not macro-innovation rates, which relate more to a population's level of general intelligence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Further, the measurement model for the latent structure of Asabiyyah was not meaningfully confounded by temporal autocorrelations, which were found to be of negligible magnitudes, nor were the lexicographically convergent results confounded with the age of the words sampled, which is significant as age has been found in previous work on Ngram viewer to be a significant predictor of temporal changes in the utilization frequencies of words (Woodley of Menie et al 2015). The developmental instability factor may therefore capture changes in the strength of negative selection on indicators that may serve as proxy measures of disturbed patterns of social epistasis.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…Further, the measurement model for the latent structure of Asabiyyah was not meaningfully confounded by temporal autocorrelations, which were found to be of negligible magnitudes, nor were the lexicographically convergent results confounded with the age of the words sampled, which is significant as age has been found in previous work on Ngram viewer to be a significant predictor of temporal changes in the utilization frequencies of words (Woodley of Menie et al 2015). The developmental instability factor may therefore capture changes in the strength of negative selection on indicators that may serve as proxy measures of disturbed patterns of social epistasis.…”
Section: Discussionmentioning
confidence: 60%
“…MLM4 involved the estimation of separate word-specific logarithmic slopes and intercepts over time. All MLMs were statistically controlled for the effects of the year of FirstUse recorded for each word in the analyses; this is an important control, as it has been found that older words tend to be better known to users of texts as a result of the lag between changes in spoken and written texts (Curzan 2009;Woodley of Menie et al 2015); LNT is the natural logarithmic function of time.…”
Section: Multilevel Modelsmentioning
confidence: 99%
See 2 more Smart Citations